2015
DOI: 10.1021/acs.jpcb.5b02898
|View full text |Cite
|
Sign up to set email alerts
|

Universality of Viscosity Dependence of Translational Diffusion Coefficients of Carbon Monoxide, Diphenylacetylene, and Diphenylcyclopropenone in Ionic Liquids under Various Conditions

Abstract: Translational diffusion coefficients of diphenylcyclopropenone (DPCP), diphenylacetylene (DPA), and carbon monoxide (CO) in 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([BMIm][NTf2]) and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([EMIm][NTf2]) were determined by the transient grating (TG) spectroscopy under pressure from 0.1 to 200 MPa at 298 K and from 298 to 373 K under 0.1 MPa. Diffusion coefficients of these molecules at high temperatures in tributylmethylphosphonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 51 publications
6
49
0
Order By: Relevance
“…This is because the bulky structure of the silyl or siloxane group slows down the movement of the cation even though the interaction between the cation and anion and the flexibility of the side chain can have an opposite effect on the viscosity. [15][16]29 This idea is supported by the SiIL diffusion coefficients measured by Chung et al 39 They found that the diffusivity of the trimethylsilylmethyl-substituted imidazolium cation is nearly identical to that of the TFSI anion, whereas cations of ILs generally move faster in AlILs. [40][41][42][43] ILs with the Si-O-Si group showed somewhat lower viscosities than those with the Si group, as was previously reported.…”
Section: Viscosity and Density Of Ilsmentioning
confidence: 86%
See 3 more Smart Citations
“…This is because the bulky structure of the silyl or siloxane group slows down the movement of the cation even though the interaction between the cation and anion and the flexibility of the side chain can have an opposite effect on the viscosity. [15][16]29 This idea is supported by the SiIL diffusion coefficients measured by Chung et al 39 They found that the diffusivity of the trimethylsilylmethyl-substituted imidazolium cation is nearly identical to that of the TFSI anion, whereas cations of ILs generally move faster in AlILs. [40][41][42][43] ILs with the Si-O-Si group showed somewhat lower viscosities than those with the Si group, as was previously reported.…”
Section: Viscosity and Density Of Ilsmentioning
confidence: 86%
“…6,[8][9][14][15] The change in intermolecular interaction is caused by change in ionic nature of the SiIL ions. [15][16]29 Hereafter, this discussion is framed in terms of these three factors. As previously suggested by Shirota et al, the flexibility of the silyl and siloxane groups affect the physical properties of ILs.…”
Section: Plausible Factors Contributing Small P For Co Diffusion Imentioning
confidence: 99%
See 2 more Smart Citations
“…[70][71][72][73] Despite noting that charge-charge interactions are much more relevant for ionic liquids as for the diffusivity of water in presence of proteins, the deviations from SE behavior are similar in origin. [70][71][72][73] Despite noting that charge-charge interactions are much more relevant for ionic liquids as for the diffusivity of water in presence of proteins, the deviations from SE behavior are similar in origin.…”
Section: Sh3 and Bsa In Mixturesmentioning
confidence: 99%